Pain Catastrophizing and Quality of Life in Adults With Chronic Rhinosinusitis. (29th January 2021) - Kazi, Aasif; West, Emma; Rahman, Shahryar; Kim, Sarah; Sima, Adam; Schuman, Theodore A.
Abstract : Objectives/Hypothesis: Psychological comorbidity is common in patients with chronic rhinosinusitis (CRS) and is correlated with decreased overall and disease‐specific quality of life (QoL). Prior research reported that anxiety and depression, as measured by the hospital anxiety and depression scale (HADS), are associated with worse CRS‐specific QoL, as assessed via the Rhinosinusitis Disability Index (RSDI). Furthermore, patients prone to anxiety/depression may display an exaggerated response to real or anticipated discomfort; the pain catastrophizing scale (PCS) is a validated instrument designed to measure this phenomenon. This study is intended to explore the role of pain catastrophizing in relation to anxiety, depression, and disease‐specific QoL in patients with facial pain attributed to CRS. Study Design: Prospective cohort study. Methods: Diagnosis of presumed CRS was based upon current American Academy of Otolaryngology – Head & Neck Surgery (AAO‐HNS) guidelines; all participants reported facial pain as a component of their CRS symptomatology. RSDI, HADS, and PCS questionnaires were administered upon presentation prior to intervention, and objective measurements of sinonasal inflammation were obtained via nasal endoscopy and computed tomography (CT). Results: Seventy‐five patients were enrolled in the study. Significant positive correlations were found between PCS and HADS, total RSDI, and RSDI emotional sub‐scores ( P  < .05). The incidence of objective evidence of disease, as measured via nasal endoscopy and CT, was not significantly different in catastrophizing patients. Conclusions: Pain catastrophizing correlates with anxiety/depression and worse disease‐specific QoL in patients meeting symptomatic criteria for CRS. Otolaryngologists should be aware that catastrophic thinking can intensify a patient's perception of sinonasal symptoms, and clinicians may consider management of psychological comorbidity to optimize rhinologic outcomes. Level of Evidence: 4 Laryngoscope, 131:1939–1945, 2021